2023
DOI: 10.3390/antiox12111921
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Hippocampal All-Trans Retinoic Acid (ATRA) Deficiency to Alzheimer’s Disease: A Narrative Overview of ATRA-Dependent Gene Expression in Post-Mortem Hippocampal Tissue

Joey Almaguer,
Ashly Hindle,
J. Josh Lawrence

Abstract: There is accumulating evidence that vitamin A (VA) deficiency contributes to the pathogenesis and progression of Alzheimer’s disease (AD). All-trans retinoic acid (ATRA), a metabolite of VA in the brain, serves distinct roles in the human hippocampus. Agonists of retinoic acid receptors (RAR), including ATRA, promote activation of the non-amyloidogenic pathway by enhancing expression of α-secretases, providing a mechanistic basis for delaying/preventing amyloid beta (Aβ) toxicity. However, whether ATRA is actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 265 publications
0
1
0
Order By: Relevance
“…Many of the identified RARβ target genes associated with these pathways have been implicated in various neurodegenerative diseases such as Alzheimer's and Parkinson's diseases [43,44]. Studies have shown that loss of RARβ can lead to mitochondrial dysfunction in mice, and that RARβ agonists can prevent mitochondrial failure induced by mitochondrial toxins, and reduce mitochondrial fragmentation and cell death [13,45]. Our results show that Ellorarxine can significantly alleviate mitochondrial dysfunction in neurons induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…Many of the identified RARβ target genes associated with these pathways have been implicated in various neurodegenerative diseases such as Alzheimer's and Parkinson's diseases [43,44]. Studies have shown that loss of RARβ can lead to mitochondrial dysfunction in mice, and that RARβ agonists can prevent mitochondrial failure induced by mitochondrial toxins, and reduce mitochondrial fragmentation and cell death [13,45]. Our results show that Ellorarxine can significantly alleviate mitochondrial dysfunction in neurons induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 56%